Genome-wide association study identifies candidate loci associated with postoperative fentanyl requirements after laparoscopic-assisted colectomy. (January 2016) - Mieda, Tsutomu; Nishizawa, Daisuke; Nakagawa, Hideyuki; Tsujita, Miki; Imanishi, Hirokazu; Terao, Kazuhisa; Yoshikawa, Hiroaki; Itoh, Kazushi; Amano, Kojiro; Tashiro, Jo; Ishii, Toshimasa; Ariyama, Jun; et al.
Aims: Opioids are widely used as effective analgesics, but opioid sensitivity is well known to vary widely among individuals and the underlying genetic factors are not fully understood, thus hampering efficient pain treatment. We explored the genetic factors that contribute to individual differences in opioid sensitivity by performing a genome-wide association study.Methods: We conducted a multistage genome-wide association study in subjects who underwent laparoscopic-assisted colectomy (LAC).Results: A nonsynonymous SNP in the LAMB3 gene region, rs2076222, was strongly associated with postoperative opioid requirements. The C allele of this best-candidate SNP was associated with lower opioid sensitivity and/or higher pain sensitivity in the patient subjects.Conclusion: Our findings provide valuable information for personalized pain treatment after LAC, in which the C allele of the rs2076222 SNP is associated with lower opioid sensitivity and requires more opioid analgesic after LAC.